PENGARUH MOTIVASI DAN KEBIASAAN BELAJAR SISWA TERHADAP HASIL BELAJAR MATEMATIKA - Rosyadi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
This research aims to determine: (1) a positive influence of student?s motivation towards      their      mathematics      learning outcomes;    (2)   a    positive    influence    of student?s       learning       habits       towards mathematics  learning  outcomes;  (3)  and  a positive  influence  of  the  student?s  between motivation and study habits combined toward mathematics     learning     outcomes.     The research   was   conducted   using   a   survey method explanation. In this research, there are three instruments. The instrument for the student?s mathematics learning outcomes is in  essay  form.  While  the  instrument  for student's motivation and study habits are in the  form  of  questionnaires.  Data  analysis technique  used  in  this  research  is  simple regression and double regression. Based on the analysis, it can be concluded that:  (1) there is a positive influence of the student's motivation     towards     their     mathematics learning  outcomes;  (2)  there  is  a  positive influence   of   the   student's   study   habits towards  their  learning  outcomes;  and  (3) there is a positive influence motivation and study  habits  of  students  combined  toward their outcomes in learning mathematics.